Structures of Hsp90α and Hsp90β bound to a purine‐scaffold inhibitor reveal an exploitable residue for drug selectivity. Issue 10 (12th June 2019) - Huck, John D.; Que, Nanette L. S.; Sharma, Sahil; Taldone, Tony; Chiosis, Gabriela; Gewirth, Daniel T.
ABSTRACT: Hsp90α and Hsp90β are implicated in a number of cancers and neurodegenerative disorders but the lack of selective pharmacological probes confounds efforts to identify their individual roles. Here, we analyzed the binding of an Hsp90α‐selective PU compound, PU‐11 ‐trans, to the two cytosolic paralogs. We determined the co‐crystal structures of Hsp90α and Hsp90β bound to PU‐11 ‐trans, as well as the structure of the apo Hsp90β NTD. The two inhibitor‐bound structures reveal that Ser52, a nonconserved residue in the ATP binding pocket in Hsp90α, provides additional stability to PU‐11 ‐trans through a water‐mediated hydrogen‐bonding network. Mutation of Ser52 to alanine, as found in Hsp90β, alters the dissociation constant of Hsp90α for PU‐11 ‐trans to match that of Hsp90β. Our results provide a structural explanation for the binding preference of PU inhibitors for Hsp90α and demonstrate that the single nonconserved residue in the ATP‐binding pocket may be exploited for α/β selectivity.